2011
DOI: 10.1371/journal.pone.0027325
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate Genome-Wide Association Analyses of Femoral Neck Bone Geometry and Appendicular Lean Mass

Abstract: ObjectiveFemoral neck geometric parameters (FNGPs), such as periosteal diameter (W), cross-sectional area (CSA), cortical thickness (CT), buckling ratio (BR), and section modulus (Z), are highly genetically correlated with body lean mass. However, the specific SNPs/genes shared by these phenotypes are largely unknown.MethodsTo identify the specific SNPs/genes shared between FNGPs and appendicular lean mass (ALM), we performed an initial bivariate genome-wide association study (GWAS) by scanning ∼690,000 SNPs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
2
11
0
2
Order By: Relevance
“…Importantly, these associations were confirmed in three replication cohorts consisting of over 6000 total white and Chinese subjects. Sun et al 57 recently identified several novel candidate polymorphisms underlying both appendicular lean mass and femoral neck geometric properties in a large GWAS in Chinese adults followed by independent replication in white subjects. Most recently, Hai and colleagues 58 performed a copy-number variation GWAS in this same Chinese cohort and identified the Gremlin1 gene as significantly associated with lean mass.…”
Section: Linkage-analysis and Genome-wide Association Studies (Gwass)mentioning
confidence: 99%
“…Importantly, these associations were confirmed in three replication cohorts consisting of over 6000 total white and Chinese subjects. Sun et al 57 recently identified several novel candidate polymorphisms underlying both appendicular lean mass and femoral neck geometric properties in a large GWAS in Chinese adults followed by independent replication in white subjects. Most recently, Hai and colleagues 58 performed a copy-number variation GWAS in this same Chinese cohort and identified the Gremlin1 gene as significantly associated with lean mass.…”
Section: Linkage-analysis and Genome-wide Association Studies (Gwass)mentioning
confidence: 99%
“…Because of this important advantage, APLM is currently widely used in assessment of a sarcopenic status of an individual 14 as well as in variety of the genetic studies, for example. 15,16 We used a large sample of middle-aged UK female twins, who were assessed using whole body DXA, metabolomic (MTB) screening and genome-wide association scans imputed to 2.5 million variants. In addition, since we were interested in accurate estimation of common and variable-specific genetic and environmental effects on LBM and its associated metabolites, we also implemented a newly developed modification of bivariate analysis, reported here for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Few of these report significant genetic associations with skeletal traits (Table II). Of the orthopaedic-related studies, the majority assessed quantitative traits such as measures of bone morphology [38][39][40][41] or bone integrity 42,43 rather than associations with the presence or absence of disease. Genetic studies directed at osteoporosis phenotypes outnumber other GWASs of diseases with orthopaedic involvement, and these have been extensively reviewed elsewhere 44 .…”
Section: Gwass For Orthopaedic Diseasesmentioning
confidence: 99%